High incidence and prevalence of multiple sclerosis in south east Scotland: evidence of a genetic predisposition. - Rothwell, P; Charlton, D (1998)
OBJECTIVE: To determine the incidence and prevalence of multiple sclerosis in the Lothian and Border Health Board Regions of south east Scotland. METHODS: Incidence study: all patients were identified in whom a diagnosis of Poser category probable or definite multiple sclerosis was made by a neurologist between 1992 and 1995. Prevalence study: all patients known to have multiple sclerosis who were alive and resident in the study area on 15 March 1995 were recorded. RESULTS: The crude annual incidence rates of probable or definite multiple sclerosis per 100000 population were the highest ever reported: 12.2 (95% confidence interval (95% CI) 10.8-13.7) in the Lothian Region and 10.1 (95% CI 6.6-13.6) in the Border Region. A total of 1613 patients with multiple sclerosis were resident in the study area, giving standardised prevalence rates per 100000 population of 203 (95% CI 192-214) in the Lothian Region and 219 (95% CI 191-251) in the Border Region. Prevalent cases were more likely than expected to have a Scottish surname (risk ratio 1.24, 95% CI 1.14-1.34). CONCLUSION: Orkney and Shetland were previously thought to have by far the highest prevalence of multiple sclerosis in the world: about double that found in England and Wales. However, the prevalence in south east Scotland is equally high, suggesting that the Scottish population as a whole has a genetic susceptibility to the disease, and undermining the hypothesis that patterns of infection specific to small sparsely populated island communities are important in the causation of multiple sclerosis.